2009
DOI: 10.1089/dna.2008.0845
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Functional Polymorphism, 16974 A/C, in the Interleukin-12-3′ Untranslated Region Is Associated with Risk of Glioma

Abstract: Genetic factors are important in the development of glioma. Interleukin-12 (IL-12) is a multifunctional cytokine that induces Interferon (IFN)-gamma secretion and plays an important role in antitumor immunity. Interleukin-27 (IL-27) is a novel IL-12 family member, and the present studies demonstrate that IL-27 mediates a potent antitumor activity. The aim of this study was to investigate whether IL-12 and IL-27 gene polymorphisms and their serum levels are associated with glioma. We analyzed IL-12 gene 16974 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
3
28
1
Order By: Relevance
“…In the present study, we found that rs3212227 AC/CC genotypes were associated with a significantly decreased risk of osteosarcoma, which were in agreement with the studies on glioma (Zhao et al, 2009) and nasopharyngeal carcinoma (Wei et al, 2009), but not the one on bladder cancer ( Jaiswal et al, 2013). The inconsistence between the present study and previous one ( Jaiswal et al, 2013) might be due to heterogeneity of cancer etiology, the profound underlying molecular mechanisms, and/or multiple environmental exposures in different ethnicities.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we found that rs3212227 AC/CC genotypes were associated with a significantly decreased risk of osteosarcoma, which were in agreement with the studies on glioma (Zhao et al, 2009) and nasopharyngeal carcinoma (Wei et al, 2009), but not the one on bladder cancer ( Jaiswal et al, 2013). The inconsistence between the present study and previous one ( Jaiswal et al, 2013) might be due to heterogeneity of cancer etiology, the profound underlying molecular mechanisms, and/or multiple environmental exposures in different ethnicities.…”
Section: Discussionsupporting
confidence: 88%
“…41 In humans, polymorphisms in the 3 0 -untranslated region of IL12A lead to decreased IL-12 production, which coincides with an increased susceptibility to develop glioblastomas. 42 Despite the remarkable anticancer activity exerted by IL-12, other members of the IL-12 family play critical roles in the regulation of tumor development (see Box 1).…”
Section: Mechanisms Of Tumor Protection Through Il-12mentioning
confidence: 99%
“…The -964A/G polymorphism (rs153109) of IL-27p28 gene promoter was first identified in a case-control study and showed a relationship with asthma susceptibility (6). After that, several case-control studies were conducted to investigate the association between IL-27p28 gene -964A/ G polymorphism and cancer risk in Chinese population (7)(8)(9)(10)(11)(12)(13)(14). However, conflicting results were observed, which might be caused by small sample size of each individual study.…”
Section: Introductionmentioning
confidence: 99%